2014
DOI: 10.1245/s10434-014-4139-y
|View full text |Cite
|
Sign up to set email alerts
|

Extramammary Paget’s Disease in Males: Survival Outcomes in 495 Patients

Abstract: Survival in men with EMPD is lower among those with distant disease and primary tumors located in the perianal region. The reasons for increasing EMPD incidence over time and for the racial disparities in disease occurrence require further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
46
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 12 publications
6
46
1
Order By: Relevance
“…Although most primary EMPDs are intraepithelial, approximately 4% to 20% primary vulvar EMPDs [14, 9, 13, 15, 16] and 26% to 61% primary penoscrotal EMPDs were invasive at the time of presentation [5, 7, 8, 10, 5861]. Some of these invasive adenocarcinomas arise from the intraepithelial EMPD (type Ib primary EMPDs) whereas others are underlying adenocarcinomas which showed secondary epidermotropism (type Ic primary EMPDs) [3, 6, 8, 9, 1416].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although most primary EMPDs are intraepithelial, approximately 4% to 20% primary vulvar EMPDs [14, 9, 13, 15, 16] and 26% to 61% primary penoscrotal EMPDs were invasive at the time of presentation [5, 7, 8, 10, 5861]. Some of these invasive adenocarcinomas arise from the intraepithelial EMPD (type Ib primary EMPDs) whereas others are underlying adenocarcinomas which showed secondary epidermotropism (type Ic primary EMPDs) [3, 6, 8, 9, 1416].…”
Section: Discussionmentioning
confidence: 99%
“…Among patients with invasive EMPDs (type Ib and type Ic), 20% to 40% had lymph node metastasis [4–7, 9, 11]. Up to 17% to 50% patients with invasive EMPDs also develop concurrent or subsequent distant metastasis [4, 5, 7, 912]. …”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the incidence of EMPD is higher among Asians than white patients based on the database of Surveillance, Epidemiology and End Results (SEER). 4 Ohara et al 5 reported that LNM in bilateral inguinal regions has a poor prognosis. In that study, the number of cases of bilateral lateral LNM was limited; however, there was no difference in prognosis between bilateral and unilateral inguinal LNM.…”
Section: Discussionmentioning
confidence: 99%
“…Extramammary Paget's disease (EMPD) is an intraepithelial adenocarcinoma which predominantly affects areas with a high apocrine gland concentration, including the vulva, perineal, perianal, scrotal, penile and axillae skin. [1][2][3] EMPD lesions are notorious for its chronic relapsing clinical course and unbearable clinical symptoms such as itching, skin ulcer and bleeding. [2,4] The standard treatment for EMPD is often extensive surgical excision followed by plastic reconstruction, which frequently leaves anatomical and functional impairments, and results in a signi cantly diminished quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…[12,13,18] In multiracial country like the United States, the incidence of EMPD showed ethnic disparity, the incidence in black males was nearly four times lower and in Asians/Paci c islander males four times higher than that in Caucasian males between 1973 and 2009. [1] No national epidemiological studies are available to estimate the prevalence and incidence of EMPD in Asian countries, including China.…”
Section: Introductionmentioning
confidence: 99%